Choosing Investment Managers - Goyal, Amit; Wahal, Sunil; Yavuz, M. D. (Journal of Financial and Quantitative Analysis, 2024)
Abstract Investment managers connected to plans sponsors are more likely to be hired than not-connected managers. The magnitude of the selection effect is comparable to that of prior performance. Ex post, connections do not result in higher post-hiring returns. Relationships are thus conducive to asset gathering by investment managers but do not generate commensurate pecuniary benefits for plan sponsors.